SUVmax-based assessment of PET response shows a superior specificity to Deauville criteria for predicting recurrence in Hodgkin's lymphoma. Issue 5 (16th April 2021) - Texte, Edgar; Lequesne, Justine; Tilly, Hervé; Jardin, Fabrice; Vera, Pierre; Stamatoullas, Aspasia; Becker, Stéphanie
Abstract: One of the limitations of 18 FDG PET/CT for therapeutic evaluation in Hodgkin's Lymphoma is the relatively high rate of false positive uptake. SUVmax reduction (ΔSUVmax ) and tumor/liver ratio (TLr) are promising tools for response assessment in lymphoma. We determined the optimal cutoff values for ΔSUVmax and TLr and compared them to Deauville score (DS) after two and four cycles chemotherapy (PET2 and PET4 respectively) and at the end of treatment PET (PETeot) on a cohort of 362 patients. TLr showed better diagnostic performances than DS for predicting 5-year progression-free survival (PFS), especially on early PET/CT assessments. Positive predictive values at PET2 for TLr, ΔSUVmax and DS were 51%, 34% and 31% respectively. On the multivariable analysis, significant predictive factors of PFS were TLr (at PET2, PET4 and PETeot) and ΔSUVmax (at PET4 and PETeot). DS was not significantly associated with PFS at any PET timing.